RESEARCH ON FATIGUE DAMAGE OF ELECTRICAL CONNECTOR JACK SPRINGS UNDER TRIAXIAL RANDOM VIBRATION CONDITIONS - WEN BaoHua; XU FengLin; ZHAO Hua; CAI YangTao; QI JiaLei; PAN Jun (Jixie qiangdu)
To address the issue of reducing the contact pressure of jack spring in the triaxial random vibration environment of electrical connectors, a finite element model was built to reveal the assembly relation of electrical connector and connection of the contact components. The finite element analysis of triaxial random vibration was conducted by the combination of HyperMesh spring, the two-dimensional joint probability distributions of mean stress and stress amplitude were established, and the equivalent load model was proposed. Based on the Miner cumulative damage criterion, the variations in the fatigue cumulative damage values for the root of the jack spring with vibration time and random vibration stress levels were plotted. The constantthat the contact pressure of the jack spring is decreased due to its increased opening diameter. The plastic deformation occurs and Ansys software. The tri-axial and tri-tangential direction stress power spectral densities at the root of the jack spring were obtained under different vibration stress levels. Based on the principle of minimum distortion energy, the theoretical equivalentcalculate the time-domain load history of the root of the jack spring. Considering the pre-stress imposed on the root of the jack stress power spectral density was achieved. Accordingly, the inverse non-uniform discrete Fourier transform was applied to stress acceleration test of electrical connector was carried out in a tri-axial random vibration environment. The results demonstrate near the root of the jack spring, while the irregular creep appears at the edge of its root end. As the position approaching to the outside, the creep trend becomes stronger and is gradually enhanced from inside to outside.